The mathematical model realization algorithm of high voltage cable - Tirshu M.S. (Problems of the Regional Energetics, 2006)
At mathematical model realization algorithm is very important to know the account order of necessary relations and how it presents. Depending of loads or signal sources connection in selected points of mathematical model its very important to know as to make the equations in this point that it was possible to determine all unknown variables in this point. The number of equations which describe this point must to coincide with number of unknown variables, and matrix which describes factors at unknown variables should be square and have dimension equal to number of unknown variables. This article shows procedure and the order of programming of this mathematical model.